Reconstruction of a large distal femoral giant cell tumor using a 3D-printed condylar support lattice metal implant and fibular grafts: a novel biomechanical and surgical approach - Aashish Chaudhry; Abhishek Kumar Sambharia; Bharat Bahre; Mani Pandey; Tanvi Chawla (3D Printing in Medicine)
Abstract Objective This study presents a novel approach to reconstructing a large defect in the load-bearing condylar region of distal femur following the surgical removal of a giant cell tumor (GCT). By using advanced 3D printing technology and virtual surgical planning, designing a patient-specific implant (PSI) to replace the defect and integrate a fibular graft for osseointegration, providing cortical bone strength. Methods A 40-year-old female patient with recurrent pain and swelling in the left knee was diagnosed with a distal femoral GCT. Imaging studies confirmed a large lytic lesion with cortical thinning. After tumor excision, reconstruction was performed using a 3D-printed lattice metal implant designed for biological and mechanical integration. A 3D printed custom titanium plate was used additionally for structural support and a fibular graft was embedded within the implant for biological union. Results Postoperative outcomes demonstrated progressive osseointegration, weight-bearing capability, and functional recovery. The patient regained maximum osseointegration with the completion of 6 months and full-strength unrestricted mobility at the end of 18 months postoperatively without recurrence. Radiographic follow-ups confirmed structural integrity and graft incorporation. Conclusion This study illustrates the successful application of a customized lattice metal implant integrated with a fibular graft, demonstrating its feasibility for large tumor-induced defects in weight-bearing regions.